Antecedentes históricos de la enseñanza-aprendizaje de la construcción textual escrita en inglés con fines médicos/Historical background of the teaching- learning of written textual construction in English for medical purposes - Nancy María Beckles Ferry; Alder Varela Viamontes; Yanet de los Ángeles Chávez de la Vega (Humanidades Médicas, 2022)
The teaching-learning process of English in medical universities has undergone study plan changes to match the demands of the society related to the integral formation of health professionals with communicative competence in English, in the oral and in the written sub-code as well. The objective of the present paper is to analyze the historical background of the written text construction in the teaching-learning process of English for medical purposes in Cuba. The methods of theoretical historical-logical level and analysis-synthesis allowed the knowledge of the main tendencies in the development of this theme and the determination of its historicity. The review of normative documents of the Medicine career and the consulted bibliography on the topic, allowed the compilation of information presented and the establishment of the main trends that have characterized the textual construction written in English for medical purposes.